La classe media va in Europa? Transnazionalismo e stratificazione sociale nell’Unione Europea - Baglioni, Lorenzo Grifone; Recchi, Ettore (SocietàMutamentoPolitica, 2013)
Supported by EU citizenship, Europeans seem to enjoy wide life chances and experiential horizons. Our hypothesis is that transnational practices (travels, social relations and lifestyles) lead to nurture a stronger identification with Europe. Empirical analysis (with Eurobarometer data of 2010) confirms the hypothesis but also indicates that “Europeanness” – in its two dimensions: practices and identifications – is stratified, being strongest in the upper social class. While the overall transnationalism-European identification association holds in all social strata as well, the middle class does not take the lead of Europeanization as it did historically when it contributed to the nation building of modern States.